The White-winged Duck Cairina scutulata in Laos - Evans, Tom D; Robichaud, William G; Tizard, Robert J (Wildfowl, 1996)
The White-winged Duck faces a high risk of global extinction in the wild in the near future. It was recorded from two regions of Laos during 1992-95. Records from six localities on the Nakai Plateau (Khammouan Province, central Laos) indicated at least nine individuals were present, and, including unsurveyed areas, the population may occupy six to 12 locations, each with one or two individuals. Fifteen adults and one brood of three young were seen at scattered sites in the southern provinces of Champasak and Attopu. Local reports suggest that the total number may be two or three times as large. Populations in both regions are in remote parts of large blocks of flatland forest. The Nakai population was mainly seen along rivers 20-30 m wide, whilst birds in the southern region were seen on shallow pools and small streams. Some observations of behaviour are presented. To date, opportunistic hunting has probably had the biggest detrimental effect on the species. Other developments, such as human population growth, road-building and hydro-electric dam-construction will reduce the available habitat and further increase hunting pressure. Prospects for conservation are discussed.